A Review of Military Research into Alcohol Consumption. Issue 2 (1st June 2011) - Verrall, Neil
Abstract : Alcohol consumption is a part of military history. The impacts in terms of both short-term and long-term consequences require modern militaries to develop and instigate a duty of care for its personnel, which informs the military's 'cradle to the grave' approach in addressing alcohol consumption and other risky health behaviours (e.g. smoking, driving, sex, drugs, obesity, etc.). Thus, in recent years there have been numerous studies that have either focused on, or included, measures of alcohol consumption among various military populations. Therefore, a synthesis of this research is warranted in order to provide a contemporary understanding of this topic. This review addresses the military research regarding alcohol consumption. It reviews the methodological issues associated with the breadth of research, as well as commenting on a range of factors that need to be considered when interpreting and comparing the different research studies; for example, (1) when comparing findings across military to civilian and pan-military populations, (2) deployment-related research, (3) military groups at risk, and (4) the impact on readiness, operational effectiveness and force sustainability.